Prevalence and factors associated with different types of intimate partner violence in Peruvian women - Dara Tiravanti-Delgado; Maria Chuquizuta-Lucero; John Barja-Ore; Natalia Valverde-Espinoza (Revista Cubana de Medicina Militar)
Introduction: Intimate partner violence is a public health problem that has a negative impact on the health status of women, and whose multifactorial origin demands the need for new comprehensive and prevention strategies. Objective: To determine the prevalence and factors associated with the different types of intimate partner violence in Peruvian women. Methods: Cross-sectional study, carried out from the 2019 Demographic and Family Health Survey, 2,518 records of women of reproductive age were analyzed. Unweighted and weighted counts were estimated, with its 95 % confidence intervals. The chi square test was used. Results: The prevalence of intimate partner violence was 57,7 %. Psychological abuse occurred in 52,8 % of women, physical abuse in 29,5 % and sexual abuse in 7,1 %. In the cases of physical violence, 21,8 % had primary education and 84,3 % reported that their partner drank alcohol. Among the women with psychological abuse, 72,7 % were between 30 and 49 years old and 80,2 % were from urban areas. Among the victims of sexual violence, 48,5 % were poor or very poor and 47 % had secondary education. Conclusions: Intimate partner violence is a very prevalent problem, which is associated with different sociodemographic factors, although sexual and physical abuse were not associated with the area of residence, nor psychological violence with age.